Rhizobium populations in grassland acid soils of southwest Spain which nodulate Trifolium, Medicago, Ornithopus and Biserrula - Temprano F.J.; Albareda M.; Rodríguez-Navarro D.N. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Legumes are important components in grasslands because they can fix atmospheric nitrogen. Clovers (Trifolium sp.), annual medics (Medicago sp.), serradella (Ornithopus sp.) and biserrula (Biserrula pelecinus) are some of the important legumes in Mediterranean pastures, which are nodulated by specific rhizobia. 24 soils from Andalucía and Extremadura regions (SW-Spain) were analysed for the presence and effectiveness, in nitrogen fixation, of native rhizobia populations for those legumes. Specific rhizobia for clovers and serradella were present in high density, in all the soils tested, but rhizobia densities for medics or biserrulla were quite variable. Even some soils were devoid of Sinorhizobium for medics. Randomly selected strains from these populations were tested for their effectiveness in nitrogen fixation with their respective host legume and they showed high fixing capacity.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)